Transformation of Cultural Landscape through Resilience Lens: A Case Study of Mae Kampong Village, Chiang Mai, Thailand - Tienthavorn, Teranetr (Nakhara : Journal of Environmental Design and Planning, 2019)
This study aims to understand the dynamics of the Mae Kampong’s cultural landscape through two intervening approaches. The study includes the cultural landscape and the community resilience. Both are examined to determine the transformations. An analysis was made of capital sources and management of resources. The methodology includes literary reviews, site observations, and interviews. The findings illustrate three periods; resilience, adaptation, and transformation. In the last phase, the community utilized their opportunities to transform into entrepreneurs. New activities emerged that included: rental houses, cafes, innovative mixed-use spaces and artisan-based shops located within the living museum sites. Sources of capital and management are varied due to their resources and their ability to obtain new knowledge and learning skills.